King Peroz’s last stand: Assessing Procopius’s account of the Hephthalite-Sasanian War of 484 - KHONSARINEJAD, Ehsan; KHORASHADI, Sorour (Historia i Świat, 2021)
In Procopius’s account of the Hephthalite-Sasanian War of 484, the Sasanian defeat is attributed to an overextended and camouflaged ditch. Over the time, some other ancient historians have retold these events with alternative and occasionally controversial details. The authors have found these narratives problematic, and based on ancient military and historical facts have questioned the historicity of the ditch story. The authors propose that the Sasanian army was either ambushed or was soundly defeated in a pitched battle. As a result, the battle survivors and the Sasanian state may have spread disinformation about the deadly ditch for lifting the lost prestige of their military machine and to keep the empire intact as its very foundation was already shaken.